Dynamic change of depression and anxiety after chemotherapy among patients with ovarian cancer. Issue 31 (August 2019) - Liu, Hongxia; Yang, Linqing
Abstract : Abstract: Psychological state of patients with ovarian cancer is worthy of attention. We aimed to investigate the levels of anxiety and depression in patients with ovarian cancer. We also investigated the dynamic changes in anxiety and depression levels after chemotherapy. A total of 228 females were included in this study. Among them, a total of 111 participants had ovarian cancer and 117 females who underwent a physical examination were selected as healthy controls. All patients enrolled were asked to fill in the Self-rating Depression Scale and the Self-rating Anxiety Scale. For patients with ovarian cancer, repeat questionnaires were measured after cycle 1 chemotherapy. The depression score of patients with ovarian cancer was 45.90 ± 10.19, significantly higher than in controls (36.08 ± 9.06, P < .001). Similar results were observed in respect of anxiety score. The score of ovarian cancer patients was 39.53 ± 12.92, significantly higher than of controls (32.15 ± 7.44, P < .001). Multivariate analyses were conducted, and the results showed that young age was the independent risk factor associated with depression among patients with ovarian cancer, while young age and singleness were the independent risk factors associated with anxiety. Repeat questionnaires were measured after chemotherapy. Interestingly, we found depression scores decreased from 45.90 ± 10.19 to 36.29 ± 8.98 after chemotherapy ( P < .001), while anxiety score increased from 39.53 ± 12.92 to 42.75 ± 9.96 after chemotherapy ( P = .009). Multivariate analysis suggested that only higher income and higher baseline depression score were the independent and most relevant risk factors associated with depression remission after chemotherapy. For patients with anxiety remission, only higher baseline anxiety score was the independent risk factor associated with anxiety remission. This study suggests that for patients with ovarian cancer, timely monitoring of the patient's psychological state, especially before and after chemotherapy treatment, is very important. Assessing the changes in the patient's psychological state, screening the population with risk factors, and prompt intervention by mobilizing social support may be effective in preventing depression and anxiety in such population.